2014
DOI: 10.1590/2317-1782/2014029in
|View full text |Cite
|
Sign up to set email alerts
|

Measuring noise in classrooms: a systematic review

Abstract: Classrooms are noisy environment and there is no standardization regarding the methodology that should be used to measure the noise in these places. Therefore, schools need to be guided constantly about the importance of acoustic adaptation in the classroom.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 10 publications
0
8
0
1
Order By: Relevance
“…The noise level used in the present study was within a suitable range that can be used during an extended period of learning. In a systematic review study [48], it has been suggested that the optimal noise level for a classroom ranges from 40 to 65 dB. Our behavioral results in Table 1 indicated that behavioral performance improved gradually from 15 to 5-dB SNR and later decreased at 0-dB SNR, as compared to the quiet (baseline) condition.…”
Section: Discussionmentioning
confidence: 57%
“…The noise level used in the present study was within a suitable range that can be used during an extended period of learning. In a systematic review study [48], it has been suggested that the optimal noise level for a classroom ranges from 40 to 65 dB. Our behavioral results in Table 1 indicated that behavioral performance improved gradually from 15 to 5-dB SNR and later decreased at 0-dB SNR, as compared to the quiet (baseline) condition.…”
Section: Discussionmentioning
confidence: 57%
“…These data corroborate the findings reported in previous studies, which have stated that the noise levels exceed those recommended by standards. [ 5 7 8 34 ]…”
Section: Discussionmentioning
confidence: 99%
“…By this, noise pollution spreads far and wide and it becomes difficult to find a quiet place [2]. In serene environments, noise is not only a nuisance, but also interferes with the performance of the activities of the area, for example, in education [3,4] and school settings, students; and teachers feel uncomfortable. While in noisy hospital, patients will be adversely affected.…”
Section: Introductionmentioning
confidence: 99%